1980
DOI: 10.2105/ajph.70.11.1202
|View full text |Cite
|
Sign up to set email alerts
|

The misuse of 'less-hazardous' cigarettes and its detection: hole-blocking of ventilated filters.

Abstract: Smokers of low-yield, ventilated-filter cigarettes sometimes defeat the purpose of the smoke-dilution holes by occluding them with fingers, lips, or tape. Blocking the holes is shown to have large effects on the delivery by these cigarettes of toxic products (nicotine, tar, and carbon monoxide). Techniques for detecting this misuse of "less hazardous" cigarettes are discussed, with particular emphasis on the distinctive signs of hole-blocking which are left in the spent filters. (Am J Public Health 1980; 70:12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
53
1

Year Published

1983
1983
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(54 citation statements)
references
References 9 publications
0
53
1
Order By: Relevance
“…We find that increases in taxes over the nineties have led to an increase 1 The epidemiological literature has paid more attention to compensatory smoking behavior. For instance, Kozlowski et al (1980) show that smokers of low yield cigarettes block ventilation holes in the filter. Jarvis et al (2001) show that smokers compensate low yield cigarettes by smoking more intensively.…”
Section: Introductionmentioning
confidence: 99%
“…We find that increases in taxes over the nineties have led to an increase 1 The epidemiological literature has paid more attention to compensatory smoking behavior. For instance, Kozlowski et al (1980) show that smokers of low yield cigarettes block ventilation holes in the filter. Jarvis et al (2001) show that smokers compensate low yield cigarettes by smoking more intensively.…”
Section: Introductionmentioning
confidence: 99%
“…For example, amino acids in dried saliva on the tipping papers reacting with ninhydrin form a pink coloration. Insertion depths ranging from 3 to 25 mm with means of 10.1 to 11.5 mm were obtained and it was concluded that ventilation hole coverage by lips during smoking depended on the position of the ventilation zone (1)(2)(3)(4)(5)(6)(7)(8).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, 95% of the ventilated filters examined showed that the vent zone was neither completely nor partially covered by smokers' lips. (1)(2)(3)(4)(5)(6)(7)(8). In these studies, mouth insertion depths were measured by a distinct color which was produced by reaction of a reagent with dried saliva residues on the cigarette butts.…”
Section: Discussionmentioning
confidence: 99%
“…The main means of achieving this improbable outcome was through the use of filter venting (King, Carter, Borland, Chapman, & Gray, 2003;Kozlowski, Frecker, Khouw, & Pope, 1980). The main effect of this is that it resulted in smokers changing the way they puff on cigarettes to ensure they received their target dose of nicotine.…”
Section: Evolution Of the Modern Cigarettementioning
confidence: 99%